Rates of MRI simulator utilisation in a tertiary cancer therapy centre. Issue 5 (10th June 2022) - Tang, Simon; Rai, Robba; Vinod, Shalini K; Elwadia, Doaa; Forstner, Dion; Moretti, Daniel; Tran, Thomas; Do, Viet; King, Odette; Lim, Karen; Liney, Gary; Goozee, Gary; et al.
Summary: Magnetic resonance imaging (MRI) is increasingly being integrated into the radiation oncology workflow, due to its improved soft tissue contrast without additional exposure to ionising radiation. A review of MRI utilisation according to evidence based departmental guidelines was performed. Guideline utilisation rates were calculated to be 50% (true utilisation rate was 46%) of all new cancer patients treated with adjuvant or curative intent, excluding simple skin and breast cancer patients. Guideline utilisation rates were highest in the lower gastrointestinal and gynaecological subsites, with the lowest being in the upper gastrointestinal and thorax subsites. Head and neck (38% vs 45%) and CNS (46% vs 67%) cancers had the largest discrepancy between true and guideline utilisation rates due to unnamed reasons and non‐contemporaneous diagnostic imaging respectively. This report outlines approximate MRI utilisation rates in a tertiary radiation oncology service and may help guide planning for future departments contemplating installation of an MRI simulator.